2023
DOI: 10.3390/polym15071738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citric Acid on Swelling Resistance and Physicochemical Properties of Post-Crosslinked Electrospun Polyvinyl Alcohol Fibrous Membrane

Abstract: A series of electrospun polyvinyl alcohol (PVA) fiber membranes were crosslinked with citric acid (CA) at concentrations of 10, 20, and 30 wt.% (designated as CA10, CA20, and CA30). The effects of CA on the chemical structure, mechanical strength, swelling resistance, and cytotoxicity of the crosslinked PVA fibrous membranes were investigated. Infrared spectroscopy indicated the enhanced esterification of carboxyl and hydroxyl groups between CA and PVA. The modulus and strength of the electrospun PVA membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…Previously, it has been reported that such behavior is ascribed to the partial modification of the polymeric structure due to the presence of the guest molecule [ 74 , 75 ]. In support of this study, Huang et al reported previously that the elastic modulus of citric acid crosslinked electrospun PVA membranes were systematically slightly lower than that of the native PVA [ 76 ]. On the contrary, the ultimate tensile strength of the samples increased up to 170% for the RPFM-1 compared to their native PVA fiber mats.…”
Section: Resultssupporting
confidence: 84%
“…Previously, it has been reported that such behavior is ascribed to the partial modification of the polymeric structure due to the presence of the guest molecule [ 74 , 75 ]. In support of this study, Huang et al reported previously that the elastic modulus of citric acid crosslinked electrospun PVA membranes were systematically slightly lower than that of the native PVA [ 76 ]. On the contrary, the ultimate tensile strength of the samples increased up to 170% for the RPFM-1 compared to their native PVA fiber mats.…”
Section: Resultssupporting
confidence: 84%
“…According to previous experimental results [ 18 ], when the CA concentration is 20 wt.%, the crosslinked PVA membrane does not degrade in the solution and maintains a good fiber shape. Therefore, CA20 was selected as the optimal concentration of CA-crosslinked PVA.…”
Section: Methodsmentioning
confidence: 62%
“…Accordingly, in the sandwich structure of multilayer membranes, the diffusion barrier through the outer layer could delay and sustain the release of the drug carried from the middle layer. Hydrogel-based electrospun membranes are considered to be an easy and effective strategy to fabricate ECM-like nanofiber structures [ 18 ]. Similarly, researchers investigated electrospun PVA/sodium alginate hydrogel composite nanofiber transdermal patches loaded with ciprofloxacin [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kemasan biokomposit PVA dengan penambahan asam sitrat memiliki struktur silang yang lebih kuat dan bersifat hidrofobik sehingga lebih rentan terhadap degradasi. (Huang, Liu, Tseng, & Chen, 2023;Nataraj, Reddy, & Reddy, 2020;Sharmin, Sone, Walsh, Sivertsvik, & Fernández, 2021).…”
Section: Penelitian Tahap IIunclassified